2022
DOI: 10.1080/21645515.2022.2129238
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to the future uptake of regular COVID-19 booster vaccinations among young adults in the UK

Abstract: The evidence of waning immunity offered by COVID-19 vaccines suggests that widespread and regular uptake of routine COVID-19 booster vaccines will be needed. In order to understand the hesitancy toward COVID-19 boosters, we examined the barriers and facilitators to receiving regular COVID-19 boosters in a sample of young adults in the UK. A cross-sectional survey was completed by 423 participants (M = 22.8; SD = 8.6 years) and assessed intention to receive regular COVID-19 boosters, the 7C antecedents of vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
4
8
0
1
Order By: Relevance
“…We found that past COVID-19 infection was commonly reported among participants and their child(ren), indicating that personal experience may contribute to participants’ perceptions of the risks of COVID-19 infection, as has been found in prior studies [ 47 , 48 , 49 , 50 , 51 , 52 ]. This is consistent with the broader literature on risk evaluation in the vaccination process, as well as the growing literature on COVID-19 booster acceptance [ 7 , 29 , 53 , 54 ]. We found hesitant adopter parents’ initial perceptions of the COVID-19 vaccine as risky remained salient for their future vaccination decisions for their children, despite previously choosing to vaccinate their child(ren).…”
Section: Discussionsupporting
confidence: 88%
“…We found that past COVID-19 infection was commonly reported among participants and their child(ren), indicating that personal experience may contribute to participants’ perceptions of the risks of COVID-19 infection, as has been found in prior studies [ 47 , 48 , 49 , 50 , 51 , 52 ]. This is consistent with the broader literature on risk evaluation in the vaccination process, as well as the growing literature on COVID-19 booster acceptance [ 7 , 29 , 53 , 54 ]. We found hesitant adopter parents’ initial perceptions of the COVID-19 vaccine as risky remained salient for their future vaccination decisions for their children, despite previously choosing to vaccinate their child(ren).…”
Section: Discussionsupporting
confidence: 88%
“…Barriers to booster acceptance may include concerns about side effects, misinformation about booster safety, logistical challenges in accessing vaccination sites, or scepticism regarding the necessity of additional doses. A detailed understanding of these barriers necessitates a comprehensive examination of individual responses and qualitative insights 37 . Healthcare policymakers can strategically address these barriers by organising health intervention programmes, such as health promotion campaigns focused on booster vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have started investigating the correlates of lower booster uptake ( Agaku et al, 2022 , Bennett et al, 2022 , Williams et al, 2022 ). Scientific studies showed that variables such as age, trust in government, and partisan self-identification, among others, correlated with booster uptake ( Rzymski et al, 2021 , Yoshida et al, 2022 , Viskupič and Wiltse, 2023 , Folcarelli et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%